Use of protein ontology to enable data exchange for complex proteomic experiments - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
Ontologies and controlled vocabularies are being established by many groups to provide roadmaps through the confused mass of data currently being generated from increasingly large-scale experimental biological experiments. The world of protein chemistry is no exception to this rule, with Protein Ontology (PO) having lead the field by providing a framework in which individual molecules and complexes can be defined by their structure, function and cellular location. PO performs searches across the protein databases using a standard nomenclature consistent to all entries.